Dynamic mechanical response and damage constitutive model of multi-flawed rocks under high strain rates - Yan, Zelin (2023)
Rocks naturally containing many flaws are frequently subjected to dynamic impact loading. Understanding the dynamic mechanical response and developing the dynamic constitutive model of flawed rocks are essentially important for the construction safety and stability assessment of rock engineering. In this study, dynamic impact tests are conducted on multi-flawed rocks with different geometries using the split Hopkinson pressure bar (SHPB). By virtue of pulse shaping technique, dynamic stress equilibrium of flawed rock specimens is well achieved. Experimental results indicate that the dynamic strength is significantly affected by both flaw geometry and strain rate. Energy dissipation density also shows strong rate-dependence and is positively correlated to dynamic strength of flawed rocks. With the aid of high-speed digital image correlation (DIC) analysis and sieve tests, progressive cracking behaviors and fragmentation characteristics of multi-flawed rocks under impact loading are comprehensively analyzed. Generally, mixed compression-shear cracking dominates the failure of flawed rocks under dynamic impact loading, and the shear cracking and fragmentation degree of specimens are promoted under higher strain rate. In addition, a dynamic damage constitutive model is proposed to characterize the dynamic strength and deformation properties of flawed rocks under high strain rates. Our proposed constitutive model comprehensively considered the effects of strain rate and coupled damage induced by micro-defects and macro-flaws on the dynamic mechanical response of flawed rocks. A good consistency of the dynamic stress–strain curves of the flawed rocks is observed between the constitutive model prediction and experimental results.